If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4x=2)+5x=30-x
We move all terms to the left:
3(4x-(2)+5x)=0
We add all the numbers together, and all the variables
3(9x-2)=0
We multiply parentheses
27x-6=0
We move all terms containing x to the left, all other terms to the right
27x=6
x=6/27
x=2/9
| -5p-9=2(p-2)-6p | | 3x-15-6x=12 | | 25+8x=9x+21 | | B+3(b+3)=5 | | -1=t-10 | | 5-(5-8n)=8n | | 9+7a-a=-3 | | -6=s-10 | | *6(5x+2)=198 | | x=-4*3-12 | | v-15=-4 | | 8x+16=-8(x+8) | | j+12=-6 | | x=-4(3)-12 | | -3z/4=18 | | Y=4(x+8)(x-6) | | b-6=5b-3b-14 | | x/3=-33 | | 4(x+2)=5(2x+3) | | 15=f+3 | | (4x+8)+(2x+2)+26.25=180 | | 3(x-2)=2x+6(x-1) | | 2=3n-1+1 | | 5x=7x/12 | | 3x=-3(x+2) | | j-5=2 | | 16=2x-x/4 | | 21x-9+53=180 | | 15m-22=-10m+28 | | Q=25-0.2p | | 3x+5=25+13x | | 17x+26=6x+x+56 |